Combining seismic and geotechnical methods to improve the prediction of physical soil properties - Alshameri, Badee (2017)
Seismic investigation offers subsurface information in a cost and time effective way compared with the geotechnical methods. The seismic data (i.e. bender element data) needs to be correlated with geotechnical data allowing it to be adopted in engineering designs. However, the procedures and analysis of bender element (BE) data can be subjected to crucial errors due to several limitations in the BE tools such as the magnitude of seismic source and frequency range. In addition, little attention had been paid to adopt field BE despite the other field seismic methods having low resolution when assessing the properties of the thin targeting layers of soil as pavement layers. Therefore, this research aim was to evaluate the limitations and reliability of BE procedure in the laboratory and the field. The research had two main stages; laboratory and model stages. In the laboratory stage, the BE limitations were assessed using homogeneous and unchanged properties of polystyrene sample instead of soil. In addition, various mixtures of sand-kaolin were investigated using the shear box, compaction and BE to obtain its empirical correlation as well as the obtained result was used to construct the soil model. In the model stage, the multi-thin layers model consisting of sand-kaolin mixtures was constructed for the purpose of suggesting the field BE procedure. The laboratory BE results recommended that the two sensors relative rotation shall be less than 50o, the position of two sensors alignment ratio between the horizontal and vertical distance shall be less than 0.5, and the effect of sample boundary occured when the ratio between the distance to sample boundary and the sample thickness less than 0.38. In model stage; the recommended procedure to be adopted in the field was via placing the BE sensors spacing less than 1 m and the BE crosshole method via placing the sensors at both side of the targeted layer was the best option. However, this method required some of the testing preparation. In conclusion, the BE limitations and procedures in the laboratory and field had been evaluated and investigated then recommended the procedures to improve the reliability of the BE results.